Beyond White Gum Valley – Knutsford Community and Stakeholder Engagement Report - Mouritz, Mike; Galloway, David (2019)
This report documents the community engagement process for the Knutsford area as part of the CRC for Low Carbon Living, Beyond White Gum Valley (BWGV – RP 3043). Some of the elements of this project also overlapped with the activities of the RENeW Nexus (Smart Cities) projects.